2012
DOI: 10.5897/ajmr11.787
|View full text |Cite
|
Sign up to set email alerts
|

Current status of vancomycin susceptibility against methicillin resistant Staphylococcus aureus (MRSA) strains: A study at two tertiary care hospitals of Pakistan

Abstract: Vancomycin has been considered mainstay treatment of infections caused by methicillin-resistant Staphylococcus aureus. The reports of the emergence of vancomycin intermediate and vancomycin resistant S. aureus from various parts of the world have been of great clinical concern. This study was performed to monitor the status of glycopeptide susceptibility against methicillin resistant S. aureus in our set up. All non-duplicate methicillin resistant Staphylococcus aureus (MRSA) isolates recovered during the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…One study from Pakistan which investigated the antibiotic resistance pattern in clinical isolates of S. aureus, reported only one isolate as vancomycin-resistant (Kaleem et al, 2012). We however found 23 out of 250 S. aureus isolates (9.2%) to be vancomycin-resistant (Table 2).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…One study from Pakistan which investigated the antibiotic resistance pattern in clinical isolates of S. aureus, reported only one isolate as vancomycin-resistant (Kaleem et al, 2012). We however found 23 out of 250 S. aureus isolates (9.2%) to be vancomycin-resistant (Table 2).…”
Section: Discussioncontrasting
confidence: 53%
“…Treatment of VRSA is challenging and these isolates are shown to be multidrug-resistant against many available antibiotics. This makes the treatment options limited, and consequently the inadequate antibiotic therapy may lead to an increased morbidity and mortality in afflicted cases (Kaleem et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been observed in the previous study. 20 Most of the studies identified the creep phenomenon by using the E test method of susceptibility testing as done in this study. 12 E test method is more reliable, sensitive and can accurately detect small MIC changings in vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…They used traditional markers over a specific period that can disguise tendencies that occur in a given setting over a period of few years. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies around the world have evaluated the comparative efficacy of the two methods using E-strip and Agar Dilution but limited work has been done in Pakistan. A study was done in Army Medical College 11 using only E-strips method to calculate VISA and VRSA rates, however, the results obtained were not compared to any of the reference methods recommended by CLSI. The comparison of the two method in our study, will also enable us to implement the best option for calculating the MIC of vancomycin in our present setup and also at the same time gives us an insight whether E-strip can be a reliable method for detecting VISA/VRSA.…”
Section: Introductionmentioning
confidence: 99%